Osteological development of the Antarctic silverfish Pleuragramma antarcticum (Nototheniidae) ... - Voskoboinikova, Olga S.; Yu Tereshchuk, O.; Kellermann, A. (Société Française d'Ichtyologie, 1994)
The paper presents a study of the osteological development of the Antarctic silverfish Pleuragramma antarcticum Boulenger (Nototheniidae). In comparison with other investigated nototheniids the development and ossification of the basioccipital and exoccipital were found to occur late in the neurocranium. The formation of the unusually large basioccipital condyle for the vertebral column and the lack of exoccipital condyle at the level of the temporal edge of the cranium are considered as distinguishing features of this species. The appearance of the bones of the ethmoidal region and certain bones of the splanchnocranium is also delayed. The projecting upper part of the cleithrum is considered a diagnostic feature of P. antarcticum. Four free pectoral radials develop from the radial cartilage, the upper subsequently fuses with the scapula. In early stages there are three pectoral interradial foramina between the radials, which close from top to bottom except the lowest. The ossification of the axial skeleton ...